2016
DOI: 10.1007/s10443-016-9554-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tow Architecture on Compaction and Nesting in Textile Preforms

Abstract: Transverse compression response of tows during processes such as vacuum infusion or autoclave curing has significant influence on resin permeability in fabrics as well as the laminate thickness, fibre volume fraction and tow orientations in the finished composite. This paper reports macro -scale deformations in dry fibre assemblies due to transverse compaction. In this study, influence of weave geometry and the presence of interlacements or stitches on the ply-level compaction as well as nesting have been inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…All three ECC TM -style fabrics are woven from a TENAX R HTA 40 3K (200 tex, Heinsberg, Germany) yarn, but in a different setting. Consequently the weight of each specific textile reinforcement will increase, thus the ondulation will increase and the nesting behaviour will change [25,26]. The yarn consists of 3000 (3k) filaments, which are characterised by a high tenacity (HT).…”
Section: Materials and Specimen Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…All three ECC TM -style fabrics are woven from a TENAX R HTA 40 3K (200 tex, Heinsberg, Germany) yarn, but in a different setting. Consequently the weight of each specific textile reinforcement will increase, thus the ondulation will increase and the nesting behaviour will change [25,26]. The yarn consists of 3000 (3k) filaments, which are characterised by a high tenacity (HT).…”
Section: Materials and Specimen Preparationmentioning
confidence: 99%
“…Especially textile reinforced composites in particular fabric, reinforced composites reveal a high inherent distribution of their geometric features-e.g., ondulation. Furthermore the textile architecture particularly ondulation affects the arrangement and vice versa [25,59]. Hence the data of the advanced analysis method presented in [26] were suitable to derive essential geometric parameters.…”
Section: Meso-scale Analysis Of Textile Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…An immediate result is the reduction in the compaction levels per individual preform thickness. Yousaf et al [23] found that the thickness of a 6-layer woven preform with nesting under typical compaction is 12% lower than the thickness at the same compaction without nesting. The tow displacement induced by nesting changes randomly local permeability and flow patterns.…”
Section: Nestingmentioning
confidence: 99%
“…The preforms were usually compacted in a large degree in order to obtain higher fiber volume fractions. Compaction behaviors of fabrics not only determine the final thickness of products, but also affect the geometrical features of fabrics [4][5][6]. Studying the compaction behavior of fabrics is therefore very important to determine processing parameter windows and predict mechanical performance.…”
Section: Introductionmentioning
confidence: 99%